FACTORS AFFECTING COCOA PRODUCTION IN BOBO VILLAGE, PALOLO DISTRICT, SIGI REGENCY - Asri, Nur; Antara, Made; Rauf, Rustam Abd (Universitas Tadulako, 2025)
The plantation commodity that is currently being intensively cultivated again by the people of Central Sulawesi is cocoa plants because the price continues to soar and its trade cannot be separated from government policies such as subsidies and Government Assistance Programs.. The purpose of this study was to determine the influence of production factors, the number of productive plants, labor, use of NPK fertilizer, labor input, age of plants, farming experience and government assistance on cocoa production in Bobo Village, and to determine the extent of the success rate of increasing cocoa production through government assistance programs in Bobo Village.. Respondents in this study amounted to 60 cocoa farmers who received assistance and those who did not receive assistance, where in determining the respondents was done by census method and Simple Random Sampling Method and to achieve the objectives of this study the analysis method used was Cobb-Douglass function analysis. The results of this study show that based on the t-test and F-test There is a significant relationship between all independent variables and cocoa production, and there is a difference in cocoa production between farmers receiving assistance and farmers who do not receive government assistance.